Pemberdayaan Koperasi Sebagai Alternatif Pembiayaan Masyarakat Desa Kare Menuju Desa Mandiri - Herawati, Novy Rachma; Susanto, Andik (Universitas Merdeka Madiun, 2021)
Abstractâ€” Cooperatives according to Law No. 25 of 1992 concerning Business Entities consisting of people or Cooperative Legal Entities by basing their activities based on Cooperative principles involved in the economic field based on family principles. There are various types of cooperatives in Indonesia, as well as cooperatives in Kare Village, Kare District, Madiun Regency, which are meant by Milk Cooperatives, KUD (Village Cooperative Units), Kopwan (Women's Cooperatives), etc. The methods used in this service are lectures, training and also mentoring. The objectives approved by this service are: a) The DesaKare community discusses the importance of cooperatives or becoming members of cooperatives related to community access can cope, b) Communities understand the process of building cooperatives and find out what should be done on cooperatives, this is a provision for the community to study cooperatives, c). Cooperative problems that have been dealt with so far, this is caused by the existence of information and assistance carried out continuously in assisting cooperatives that have difficulties, d) Growing public awareness of access that requires funds from banks in this strict financing and maintenance either in collateral or filling in Monitoring by Bank Indonesia (BI), e). The community becomes educated in this case is in choosing the management of the cooperative so that cooperative problems can be minimized, f). Revive the spirit of mutual cooperation and help each other in the community through cooperative assistance and also foster enthusiasm in deliberation in decision making.Â Keywordsâ€”: Cooperatives; Village Communities; Financing.